The Effect of Counseling using decision-making tools for family planning on interest in using the IUD - Gita Regista Pakaya; Dwi Nur Octaviani Katili; Siskawati Umar (Journal of Community Health Provision, 2021)
Increasing the used of long-term contraception method of Intra Uterine Device (IUD)user required a good and quality counseling between the client and the provider (medical personnel). The research amis to determine the effect of counseling using decision-making tools for family planning on the interest in using IUDs in Dr. M.M. Dunda Hospital, Limboto District. The research type is Quasi Experiment, the population of all pregnant women who are admitted to Dr. M.M. Dunda Limboto. The sample was all 22 pregnant women who came in April 2020 which were divided into two groups, the intervention group and the control group. Sampling technique used accidental sampling. Data collected using a check list sheet and using chi square analysis. The results showed that X2 count> X2 table (6.6> 3,841) then H0 was rejected and Ha was accepted, so it could be concluded that there was an effect of counseling using ABPK on the interest in using IUDs in Dr. M.M. Dunda Hospotal, Limboto District.